2013
DOI: 10.1080/0361526x.2013.833883
|View full text |Cite
|
Sign up to set email alerts
|

Beginning the Conversation: Discussing Scholarly Communication

Abstract: Since the earliest scholarly journals began, journal literature answered a need to communicate scholarly and scientific findings and preserve a validated scholarly record of accomplishments and areas for further research. Scholars are profoundly interested in the transformation of scholarship and the implications for their disciplines. Librarian expertise within the digital serials realm and partnering with faculty to prioritize learning in the library will imaginatively create opportunities for learning with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Initiating a dialog between disciplinary faculty and librarians, based on common interests in scholarship, would enhance the role of the academic librarians to the benefit of both the library and the academic community. To fulfill the vision of Wiegand [57] of the library as a learning space centered on the educational mission and integrated into learning and scholarship activities, academic librarians should learn more about how scholars and students work and improve their collaborative relationships with the faculty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initiating a dialog between disciplinary faculty and librarians, based on common interests in scholarship, would enhance the role of the academic librarians to the benefit of both the library and the academic community. To fulfill the vision of Wiegand [57] of the library as a learning space centered on the educational mission and integrated into learning and scholarship activities, academic librarians should learn more about how scholars and students work and improve their collaborative relationships with the faculty.…”
Section: Discussionmentioning
confidence: 99%
“…While academic librarians may potentially contribute to scholarly communication in the digital era, it is still unclear to what extent the faculty members and the academic librarians themselves understand and materialize this potential. It was shown that faculty members are receptive to collaborations with librarians and that liaison visits to the faculty increase the extent to which faculty members use the library's resources and services, making them more aware of the convergence between what they need as teachers and researchers and what the library can offer [57]. Currently lacking, however, are qualitative and quantitative data that describe how faculty members and librarians in today's academic institutions perceive the function of academic librarians and their integration into the process of scholarly communication.…”
Section: Perceptions Of Scholarly Communication In the Academic Libramentioning
confidence: 99%